Single/joint effects of pyrene and heavy metals in contaminated soils on the growth and physiological response of maize (Zea mays L.) - Wang, Yuhui; Imran, Muhammad A.; Zhao, Juanjuan; Sultan, Muhammad; Li, Manjie (Frontiers in Plant Science, 2024)
The ubiquitouswidespread presence distribution of polycyclic aromatic hydrocarbons (PAHs) and toxic heavy metals in soils is causing detrimentalhaving harmful effects on food crops and the environment. However, the defense mechanisms 2 and capacity of plants to counteract these substances have not been comprehensively explored, necessitating a systematic categorization of their inhibitory effects.Accordingly, an experimental investigation was conducted to examine the growth and physiological response of maize (Zea mays L.) to different concentrations and combinations of pyrene, copper (Cu), and cadmium (Cd), with an indicator developed to assess the joint stress. The results showed that 57-day culture with contaminations significantly inhibited the plant biomass via causing root cell necrosis, inducing lipid peroxidation, and damaging photosynthesis. The inhibition Cd (50-100 mg/kg) induced by Cd (50-100 mg/kg) appeared to be stronger inhibition than Cu (800-1000 mg/kg) under both single and joint stress, and their co-existence further aggravated the adverse effects and generated synergetic inhibition. Although the presence of pyrene at a low concentration (5-50 mg/kg) can somewhat diminish the metal stress, the elevated pollutant concentrations (400-750 mg/kg pyrene, 50-100 mg/kg Cd, and 800-1000 mg/kg Cu) switched the antagonistic effect to additive inhibition on maize growth. A satisfactory tolerance of a low-level pyrene and/or metal stress was determined, associated with a relative stability of chlorophyll-a (Chl-a) content and antioxidant enzymes activity. Nevertheless, the photosynthesis and antioxidant system were significantly damaged with increasing contaminant concentrations, resulting in chlorosis and biomass reduction. These findings could provide valuable knowledge for ensuring crop yield and food quality as well as implementing soil phytoremediation.